Surface functionalization of oil palm empty fruit bunch (OPEFB)-derived cellulose as a carboxyl platform for metal cations and dyes removal from aquatic media - Sjahro, Noerhidajat; Yunus, Robiah; Abdullah, Luqman Chuah; Abdul Rashid, Suraya; Asis, Ahmad Jaril; Kania, Dina; Karim, Alsultan (University of Malaya, 2024)
The abundant oil palm empty fruit bunch (OPEFB) as by-product of palm oil milling processes exhibits a potential as an alternative cellulose feedstock for bio-adsorbent. This study aimed to produce a highly carboxylated bio-adsorbent for direct industrial application from OPEFB-based cellulose via mercerization and followed by esterification with succinic anhydride (SA) to enhance its adsorptive capability towards hazardous heavy metal and dyes ions. The modification using SA provides the carbon backbone platform for carboxyl group attachment for the contaminants. The results showed that the carboxylated cellulose had a high carboxyl content (4.39 mmol/g). Carboxylated cellulose had a higher binding capacity for adsorbates, with removal rates of 94.7%, 97.85%, 40.9%, and 90.15% for dye, Pb2+, Cu2+, and Cd2+ cations, respectively, at pH 6, 4 hours reaction time, and at room temperature. In comparison, unmodified cellulose removed only 47%, 23.1%, 2.9%, and 7.5% for dye, Pb2+, Cu2+, and Cd2+ cations, respectively. The adsorption kinetics study revealed that the adsorption process followed the pseudo-second-order model. The adsorption isotherm of these two metal cations follows the model of Langmuir very well, while Cu2+ follows the Freundlich model. Our method produces bio-adsorbents with high carboxyl content and adsorption rate in a short reaction time using OPEFB as a green precursor material that is easily scalable for industrial use.